2023
DOI: 10.1007/s00277-023-05412-1
|View full text |Cite
|
Sign up to set email alerts
|

High prevalence of past hepatitis B virus infection in diffuse large B cell lymphoma: a retrospective study from Italy

Marcella Visentini,
Andrea Pica,
Giancarlo D’Ippolito
et al.

Abstract: Studies from high endemic areas, mostly China, indicate that surface antigen positive (HBsAgpos) chronic hepatitis B virus (HBV) infection is associated with an increased risk of developing diffuse large B-cell lymphoma (DLBCL), whereas studies in low endemic areas have provided conflicting results. Past infection, serologically defined by negative HBsAg and positive anti-core antibody (HBsAgnegHBcAbpos), has also been suggested to increase the risk of B-cell non-Hodgkin’s lymphoma (NHL) in high endemic areas.… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
2
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(2 citation statements)
references
References 28 publications
0
2
0
Order By: Relevance
“…It has been reported that ongoing HBV infection can potentiate the resistance to S-phase arrest, causing a resistance to chemotherapeutic agents [ 86 ]. The frequency of past HBV infections in a large DLBCL cohort is reported to be 16.8% by an Italian study [ 22 ]. It has been documented that past HBV infection increases the chances of developing DLBCL with an odds ratio of 2.25 [ 82 ].…”
Section: Viral Infectionsmentioning
confidence: 99%
“…It has been reported that ongoing HBV infection can potentiate the resistance to S-phase arrest, causing a resistance to chemotherapeutic agents [ 86 ]. The frequency of past HBV infections in a large DLBCL cohort is reported to be 16.8% by an Italian study [ 22 ]. It has been documented that past HBV infection increases the chances of developing DLBCL with an odds ratio of 2.25 [ 82 ].…”
Section: Viral Infectionsmentioning
confidence: 99%
“…Studies have found that HBV infection increased the risk of non-Hodgkin lymphoma and that the positive rate of HBsAg in non-Hodgkin lymphoma was 2–3 times higher than in the healthy population. 4 , 5 Some research data has suggested that HBV infection may affect patient outcomes,but other researchers have proposed different views. 6 , 7 Lemaitre’s study suggested that HBsAg(-) cases and HBsAg (+) cases had a similar survival time, and viral infection did not affect the prognoses of patients.…”
mentioning
confidence: 99%